Deformation of leukaemia cell lines in hyperbolic microchannels: investigating the role of shear and extensional components. Issue 14 (22nd June 2020) - Piergiovanni, Monica; Galli, Valeria; Holzner, Gregor; Stavrakis, Stavros; DeMello, Andrew; Dubini, Gabriele
Abstract : Experimental and computational methods: together to disentangle the role of extensional and shear fluid dynamics on single cell deformation. Abstract : The mechanical properties of cells are of enormous interest in a diverse range of physio and pathological situations of clinical relevance. Unsurprisingly, a variety of microfluidic platforms have been developed in recent years to study the deformability of cells, most commonly employing pure shear or extensional flows, with and without direct contact of the cells with channel walls. Herein, we investigate the effects of shear and extensional flow components on fluid-induced cell deformation by means of three microchannel geometries. In the case of hyperbolic microchannels, cell deformation takes place in a flow with constant extensional rate, under non-zero shear conditions. A sudden expansion at the microchannel terminus allows one to evaluate shape recovery subsequent to deformation. Comparison with other microchannel shapes, that induce either pure shear (straight channel) or pure extensional (cross channel) flows, reveals different deformation modes. Such an analysis is used to confirm the softening and stiffening effects of common treatments, such as cytochalasin D and formalin on cell deformability. In addition to an experimental analysis of leukaemia cell deformability, computational fluid dynamic simulations are used to deconvolve the role of the aforementioned flow components in the cell deformation dynamics. In general terms, the current study can be used as a guide for extracting deformation/recovery dynamics of leukaemia cell lines when exposed to various fluid dynamic conditions.